The opioid fix: America's addiction crisis and the solution they don't want you to have - Andraka-Christou, Barbara (Johns Hopkins University Press, 2020)
The author blames part of the US opioid crisis on policy that espouses abstinence-focused treatment for people addicted to opioids. The author tells the stories of people in recovery and argues that medication-assisted treatment, or MAT, needs to be available to anyone suffering from opioid abuse. The interrelated barriers to MAT-from physicians who won't prescribe it, to drug courts that mandate counseling (and counselors who deride it), to politicians who ban it-demonstrate ill-advised narrow-mindedness in the author's view.